2023
DOI: 10.1021/acs.langmuir.3c01394
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of the Effects of Salt Concentration and pH on the Self-Assembly of Kaolin Nanoplatelets

Xiong-ying Ma,
Zhao Xia,
Chen-xi Su
et al.

Abstract: Diffusion of pollutants in the earth's strata threatens both the environment and human health. The clay soil microstructure that plays a crucial role in the diffusion of pollutants is significantly influenced by the pore water chemistry. However, there is still a lack of quantitative evaluation of pore water chemistry on clay fabric evolution. To bring new insights, we systematically examined the impact of water chemistry (mainly refers to salt ion concentration and pH) on the self-assembly form (fabric) of ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…Moreover, the sedimentation behavior of kaolinite platelets exhibited notable variations in response to fluctuations in environmental salt ion and pH. The microstructure study findings revealed differences in the compactness of clay orientation, with a distinct order observed in salt (kaolin book), alkaline (face-to-face repulsion), water, and acidic condition (randomly face-to-face). , …”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the sedimentation behavior of kaolinite platelets exhibited notable variations in response to fluctuations in environmental salt ion and pH. The microstructure study findings revealed differences in the compactness of clay orientation, with a distinct order observed in salt (kaolin book), alkaline (face-to-face repulsion), water, and acidic condition (randomly face-to-face). , …”
Section: Introductionmentioning
confidence: 90%
“…The microstructure study findings revealed differences in the compactness of clay orientation, with a distinct order observed in salt (kaolin book), alkaline (face-to-face repulsion), water, and acidic condition (randomly face-to-face). 26 , 27 …”
Section: Introductionmentioning
confidence: 99%